The Ongoing CPEC-CIPEC Connectivity and the Promotion of Central Asia as a Hub for Southeast Asia - Santos, T. B.; Borges, D. (State Building and Fragility Monitor, 2024)
In recent years, there has been a significant increase in Chinese-led connectivity projects within the Belt and Road Initiative between South-Central Asia and Southeast Asia, which have directly or indirectly linked the two regions. In the heartland of Asia, the Central Asian Republics (CARs) are the primary beneficiaries of this connectivity, mainly due to their geographical location and due to the fact that the region is landlocked and, therefore, dependent on transport connectivity. Among the CARs, Kazakhstan and Uzbekistan are the main recipients of BRI-led investment in transport infrastructure and the connectivity it provides. As such, this paper aims to demonstrate that China has been promoting interregional continental connectivity as a viable alternative to maritime routes. This strategy benefits the state-building process in Kazakhstan and Uzbekistan by fostering their economic growth, which allows for social stability and state cohesion